Best practice policy statement on urodynamic antibiotic prophylaxis in the non‐index patient. Issue 4 (27th March 2017) - Cameron, Anne P.; Campeau, Lysanne; Brucker, Benjamin M.; Clemens, J. Quentin; Bales, Gregory T.; Albo, Michael E.; Kennelly, Michael J.
Abstract : Aims: Antibiotic prophylaxis before urodynamic testing (UDS) is widely utilized to prevent urinary tract infection (UTI) with only limited guidance. The Society of Urodynamics, Female Pelvic Medicine, and Urogenital Reconstruction (SUFU) convened a Best Practice Policy Panel to formulate recommendations on the urodynamic antibiotic prophylaxis in the non‐index patient. Methods: Recommendations are based on a literature review and the Panel's expert opinion, with all recommendations graded using the Oxford grading system. Results: All patients should be screened for symptoms of UTI and undergo dipstick urinalysis. If the clinician suspects a UTI, the UDS should be postponed until it has been treated. The first choice for prophylaxis is a single oral dose of trimethoprim‐sulfamethoxazole before UDS, with alternative antibiotics chosen in case of allergy or intolerance. Individuals who do NOT require routine antibiotic prophylaxis include those without known relevant genitourinary anomalies, diabetics, those with prior genitourinary surgery, a history of recurrent UTI, post‐menopausal women, recently hospitalized patients, patients with cardiac valvular disease, nutritional deficiencies or obesity. Identified risk factors that increase the potential for UTI following UDS and for which the panel recommends peri‐procedure antibiotics include: known relevant neurogenic lower urinary tract dysfunction, elevated PVR, asymptomatic bacteriuria, immunosuppression, age over 70, and patients with any indwelling catheter, external urinary collection device, or performing intermittent catheterization. Patients with orthopedic implants have a separate risk stratification. Conclusions: These recommendations can assist urodynamic providers in the appropriate use of antibiotics for UDS testing. Clinical judgment of the provider must always be considered.